Re-evaluating Byung-Chul Han’s Stance against the Aesthetics of the Smooth in Jeff Koons’ The Balloon Dogs - Kongkrit Triyawong (Journal of Integrative and Innovative Humanities)
This article analyses the critical stance of Byung-Chul Han towards the aesthetics of the smooth as it is epitomized by Jeff Koons’ Balloon Dogs. In his critique of Neoliberalism, Han argued that arts are the Other that contests the consumption and velocity of the digital age. Accordingly, Han devalued arts to be merely within the contemplative stance. The vita contempletiva is positioned as a contesting vita activa that devalues human beings to be simply animal laborans that exploit themselves in the achievement society. Art demands distance and contests lustful touch. Consequently, Han praised only certain genres of arts and ignored the potentials of contemporary arts which could point out political issues in public domains. In order to solve this problem, the author proposes two following arguments: Ways out to solve the problem in this digital age that affects the lives of human beings can be considered within the framework of contemporary arts, and to redeem human beings from exploitation in the capitalist working environment requires struggling for recognition through arts.